Tracking the Late Devonian high-P metamorphic belt in the Variscan Orogen: New constraints on the PT evolution of eclogites from the Cubito-Moura Unit (SW Iberian Massif) - Novo-Fernandez, I. (2022)
The Cubito-Moura Unit is a high-P metamorphic succession that occurs in the southern part of the Ossa-Morena Complex (SW Iberian Massif). It includes a series of metasedimentary, metafelsic and metamafic rocks affected by a high-P, low to intermediate-T metamorphic event during Late Devonian times. Geochemistry of the metabasic rocks reveals that the generation of the protoliths occurred in a supra-subduction zone setting during Late Ediacaran to Early Ordovician times, either in a back-arc or fore-arc context. The eclogites contain atoll-like garnets, omphacite, amphibole, phengite (up to Si = 3.38 apfu), paragonite, rutile and quartz. Thermodynamic modelling in the MnNCKFMASTH system indicates a high-P metamorphic event at ~24 kbar and ~ 585 °C followed by a thermal peak at ~19 kbar and ~ 630 °C, and a subsequent exhumation to ~15 kbar. This P-T path indicates deep subduction at c. 370 Ma of this arc-related section. The lithostratigraphy and tectonothermal evolution of the Cubito-Moura Unit are equivalent to that of a number of units along the Iberian, Armorican and Bohemian massifs that can be correlated as a part of the same Basal Allochthonous Terrane. These units define a single Late Devonian high-P, low- to intermediate-T metamorphic belt developed during the first stages of the Variscan Orogeny.